ARABIC STUDENTS’ PREFERENCES IN CHOOSING REFERENCES FOR THESIS WRITING - Kamal Yusuf; Robiatul Adawiyah; Siti Zulfa Ulin Nuha (Erudio Journal of Educational Innovation, 2022)
The aim of this article is to investigate the PBA UINSA students’ preferences of Indonesian references over Arabic references, despite the fact that their theses are entirely written in Arabic. This study used a qualitative research method. The data collection tehniques performed by observation, interviews, and documentation. The findings of this study revealed that the problems faced by the students  of PBA at UINSA in choosing references were as follows: the themes and methods chosen greatly influenced the choice of references, a lack of foreign language vocabulary mastered caused students the need to use Indonesian references, and many references accessible in Indonesian language related to the learning process in Indonesia during the pandemic. Furthermore, when writing the thesis, particularly in the methodolgy section, it was found that a number of references were taken from Indonesian sources. This was done because employing Indonesian references made the subject easier to understand than using foreign-language references.